Implementasi Gerakaan Literasi Dalam Meningkatkan Minat Baca Peserta Didik Di TK Melati Kecamatan Pegerageung Kabupaten Tasikmalaya - Eet Rohayati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The background of this research is that the implementation of the literacy movement will encounter several obstacles caused by various factors both from outside and from within. An institution will be able to run its superior program, if the program is carried out properly and in a structured manner, and can overcome various obstacles that arise in program activities implementing the literacy movement. With the competence of school principals and teachers who are qualified, it is hoped that students' interest in reading will also increase. The purpose of this research is to analyze and describe: 1) Implementation of the literacy movement in increasing students' interest in reading; 2) The obstacles faced in implementing the literacy movement in PAUD in order to increase students' interest in reading; 3) Efforts made by school principals and teachers in implementing literacy movement competencies to increase students' interest in reading. The research method used in the preparation of this thesis is descriptive with a qualitative approach. Data collection techniques were carried out through interviews, observation, and documentation studies. The informants in this study included school principals, supervisors, teachers, and parents of students. The results of the study show that 1) the implementation of the literacy movement program in increasing students' interest in reading is the initial foundation for introducing literacy for early childhood. The implementation of the literacy movement is at the habituation stage and can be upgraded to the development stage by involving various parties. 2) the obstacles encountered in implementing the school literacy movement are: (1) low teacher awareness, (2) the number of suitable children's reading books is difficult to find, (3) teachers are lazy to read, (4) teachers do not understand the implementation of literacy movement, and ( 5) schools lack funds, and 3) there are efforts made by schools in implementing the school literacy movement program including: (1) participating in various trainings both online and offline, (2) adding enrichment books to schools through purchasing and applying for grants, (3) bringing books closer to school members by creating several reading areas and creating an environment rich in text, (4) carrying out various forms of literacy activities, and (5) involving the public in implementing literacy movements.